Reliability-Based Topology Optimization: An Extension of the SESO and SERA Methods for Three-Dimensional Structures - Simonetti, Hélio Luiz; Almeida, Valério Silva; Das Neves, Francisco de Assis; Almeida, Vírgil Del Duca; Neto, Luttgardes de Oliveira [UNESP] (MDPI, 2022)
This study takes an approach to reliability-based topology optimization (RBTO) for 3D structures by applying an expansion of smoothing evolutionary structural optimization (SESO) and sequential element rejection and admission (SERA) for three-dimensional optimization. In the search for the stable optimal solution, and a more reliable structure, we present a performance index with the ability to monitor the evolutionary optimization procedure and adopt the filtering scheme usually applied in solid isotropic material with penalization (SIMP). The limit state functions are the maximum displacement constraints imposed in the topology optimization procedure and a structure’s performance control; a comparative analysis of the deterministic topology optimization (DTO) with the RBTO models is also explored. The obtained results suggest the importance of using the RBTO concept in 3D structures as part of the design analysis process.
Keywords: ESO; evolutionary methods; reliability-based topology optimization; SERA; SESO